At the Border: Coaching a Client with Dissociative Identity Disorder - Francine Campone (International Journal of Evidence Based Coaching and Mentoring, 2014)
Coaching/psychotherapy boundaries have been explored theoretically and through surveys. The confidential nature of coaching has precluded direct observation of how they are operationalized. The case presented here was initiated at the invitation of a client who has a clinical diagnosis of Dissociative Identity Disorder and her coach. Their journals, interviews and observed sessions enabled the author to construct a case study that offers insight into how an individual coach and client navigate the coaching/psychotherapy boundaries in practice. The case provides evidence of specific coach and client characteristics and coaching strategies employed in these circumstances.